PENGARUH PERUBAHAN TEMPERATUR TERHADAP KEKESATAN JALAN PADA PERKERASAN LENTUR - Aprizaldy, Fitra; Sulandari, Eti; Mayuni, Siti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
Road is an important infrastructure to support transportation activities. Roads are the most commonly used transportation facilities by most people. Traffic problems that impact on the weakening of some sectors, especially the economy, so the road also affects the safety, comfort, and safety of driving. Good road planning affects the level of road performance, where the plan has the highest pavement of flexible pavement or asphalt, where the asphalt has skid resistance value. The purpose of the researcher is to find the influence of temperature against the aggression on ther road which affect the safety, comfort, and safety of the rider.In this study, the data obtained by conducting a survey on the road using a tool called BPT (Bristish Pendulum Tester) is a pendulum with a rubber under it that touches to the surface of the pavement. The appointed time is in the morning, afternoon, and evening. The road used is a road that has the same pavement that is Jl. Ahmad Yani and Jl. Tanjungpura. From the results of the survey will be calculated and analyzed so that will get the effect of temperature against the road aggression.The road aggression value is indicated by BPN (British Pendulum Number) which is the value indicated by the gauge on the BPT device when the rubber touches the frictionless surface of the pavement. Based on previous research BPN values are influenced by temperature, if the temperature is low which makes the surface of pavement also low, makes BPN value tend to be higher, and vice versa.Â Keywords : Road Aggression Test , Skid Resistance